Assessment of the Association Between Clinical and Laboratory Parameters and Past Coronavirus Infection in Patients with Coronary Artery Restenosis - G. B. Batenova; E. I. Dedov; A. Yu. Orekhov; A. A. Dyussupov; D. G. Ygiyeva; M. R. Pivin; A. M. Manatova; L. M. Pivina (Архивъ внутренней медицины)
Understanding the risk factors for coronary in-stent restenosis is particularly important in patients with coronavirus disease (COVID-19). Such patients require careful monitoring, priority treatment, and prevention.The aim of our study was to assess the association between clinical and laboratory parameters and previous coronavirus infection in patients with coronary artery restenosis.Materials and methods. A cross-sectional study was conducted on a continuous sample of patients with coronary artery disease who underwent repeated myocardial revascularization in the period from 2020 to 2023 (931 patients). 420 patients in the main group had coronary artery stent restenosis, of which 162 (38.5 %) had suffered from coronavirus infection (CVI). The control group included 511 patients with repeated myocardial revascularization without stent restenosis, of whom 107 (20.9 %) had undergone CVI. Laboratory tests included troponin I, D-dimer, creatine kinase (CK), creatine kinase-MB (CK-MB), serum creatinine and glucose, C-reactive protein (CRP), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and fibrinogen, IgG and IgM antibodies to coronavirus and RNA detection by polymerase chain reaction. Statistical calculations were performed using SPSS version 20.0 software.Results: It was established that there were statistically significantly higher levels of IgG antibodies to coronavirus and C-reactive protein in the main study group compared to the control group. When dividing the study groups into subgroups of individuals with and without previous CVI, statistically significant differences in troponin levels were found (p<0.001): between the level in the group with restenosis and CVI compared to groups without restenosis with CVI, with restenosis without CVI, and in groups with revascularization without CVI and with restenosis without CVI. The levels of D-dimer, CPK, CPK-MB, CRP, and APTT had statistically significant differences in the groups with previous CVI compared to the groups without CVI. The results of multiple regression analysis indicated a statistically significant positive relationship in the study groups between the development of myocardial infarction and such indicators as CRP, blood glucose, low-density lipoproteins (LDL), previous CVI, as well as a negative relationship with left ventricular ejection fraction and high-density lipoproteins (HDL). The role of these predictors in the development of myocardial infarction was confirmed using ROC analysis.Conclusion: The results of our study indicated a relationship between previous coronavirus infection and an increased risk of coronary artery restenosis in patients with previous myocardial revascularization.